Proveedores, Impedimentos y Tribunal de Contrataciones del Estado. Reflexiones sobre la posición del Tribunal de Contrataciones del Estado respecto de quien puede y quien no puede ser proveedor del Estado - Martínez Zamora, Marco Antonio (2015)
The present article explains the main impediments for being a supplier of State in the actual regulation for public procurements. Then, the author analyses the way a wrong interpretation of the law can turn into a distortion of the legal propose, bringing a number of barriers that, in practice, affect the main goal the public procurement.